2017 25th European Signal Processing Conference (EUSIPCO) 2017
DOI: 10.23919/eusipco.2017.8081526
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of vocal emotion conversion on modulation spectrogram for simulated cochlear implants

Abstract: Abstract-Cochlear implant (CI) listeners were found to have great difficulty with vocal emotion recognition because of the limited spectral cues provided by CI devices. Previous studies have shown that the modulation spectral features of temporal envelopes may be important cues for vocal emotion recognition of noise-vocoded speech (NVS) as simulated CIs. In this paper, the feasibility of vocal emotion conversion on a modulation spectrogram for simulated CIs for correctly recognizing vocal emotion is confirmed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…These studies found that significant cues for perception of non-linguistic information are temporal modulation components of the noise-vocoded stimuli lower than the modulation frequency of 8 Hz. These studies also suggested that recognition of vocal-emotion and speaker individuality using the NVS scheme with NH listeners can be used to predict the response from CI listeners as CI simulators [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…These studies found that significant cues for perception of non-linguistic information are temporal modulation components of the noise-vocoded stimuli lower than the modulation frequency of 8 Hz. These studies also suggested that recognition of vocal-emotion and speaker individuality using the NVS scheme with NH listeners can be used to predict the response from CI listeners as CI simulators [24][25][26].…”
Section: Discussionmentioning
confidence: 99%